Stability of switched nonlinear time-delay systems with stable and unstable subsystems. (May 2017) - Tian, Yazhou; Cai, Yuanli; Sun, Yuangong
Abstract: This paper investigates the stability of switched nonlinear time-delay systems with stable and unstable subsystems. Several stability criteria are presented by resorting to novel inequality technique and average dwell time approach, which relax the assumptions that all subsystem matrices are commutative pairwise and Hurwitz stable. Finally, two numerical examples are provided to illustrate the effectiveness of the theoretical results.